2012
DOI: 10.1242/jeb.082586
|View full text |Cite
|
Sign up to set email alerts
|

Biodynamics of climbing: effects of substrate orientation on the locomotion of a highly arboreal lizard (Chamaeleo calyptratus)

Abstract: SUMMARYArboreal substrates differ not only in diameter, but also in continuity and orientation. To gain more insight into the dynamics of small-branch locomotion in tetrapods we studied the veiled chameleon walking on inclined and declined perches of up to 60deg slope. We found that forelimbs and hindlimbs contribute equally to the bodyʼs progression along inclines and declines. The higher-positioned limbʼs vertical impulses decreased with slope. And although vertical impulses in the lower-positioned limb inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…In models of climbing that describe how limbs should function, forces along the long axis of the support (the equivalent of braking and propulsive forces during walking) should also differ from that of walking in that the forelimbs and hindlimbs should both be propulsive (move the animal up the support). Researchers have found that lizards exhibit strong functional limb differentiation with respect to 'pushing' and 'pulling' (normal load in and out of the plane of support), and that both limbs function to propel the body upwards to the same degree during purely vertical movement and highly inclined movement (Autumn et al, 2006;Krause and Fischer, 2013;Wang et al, 2015a, b). In comparison, during horizontal locomotion, the forelimbs and hindlimbs of lizards propel the body forward to the same degree, but the forelimbs bear more weight than the hindlimbs (Krause and Fischer, 2013;Wang et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In models of climbing that describe how limbs should function, forces along the long axis of the support (the equivalent of braking and propulsive forces during walking) should also differ from that of walking in that the forelimbs and hindlimbs should both be propulsive (move the animal up the support). Researchers have found that lizards exhibit strong functional limb differentiation with respect to 'pushing' and 'pulling' (normal load in and out of the plane of support), and that both limbs function to propel the body upwards to the same degree during purely vertical movement and highly inclined movement (Autumn et al, 2006;Krause and Fischer, 2013;Wang et al, 2015a, b). In comparison, during horizontal locomotion, the forelimbs and hindlimbs of lizards propel the body forward to the same degree, but the forelimbs bear more weight than the hindlimbs (Krause and Fischer, 2013;Wang et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that lizards exhibit strong functional limb differentiation with respect to 'pushing' and 'pulling' (normal load in and out of the plane of support), and that both limbs function to propel the body upwards to the same degree during purely vertical movement and highly inclined movement (Autumn et al, 2006;Krause and Fischer, 2013;Wang et al, 2015a, b). In comparison, during horizontal locomotion, the forelimbs and hindlimbs of lizards propel the body forward to the same degree, but the forelimbs bear more weight than the hindlimbs (Krause and Fischer, 2013;Wang et al, 2015a,b). This latter pattern of vertical force distribution is typical of walking in most mammals with the exception of most primates, who show the reverse pattern (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in limb posture suggest weight transfer towards the hindlimbs (Lee et al, 2004;Krause and Fischer, 2013), although why that might occur as a consequence of tail loss remains unclear. Electromyography could reveal whether such a postural shift permits the lizard to engage larger muscle groups for stabilization or facilitating greater running speeds.…”
Section: Kinematic Changes Associated With Tail Lossmentioning
confidence: 99%
“…It is unclear what role this suggests, but this could imply that the gastrocnemius simply is not recruited as much during stance to propel the relatively slowmoving leopard geckos. Although chameleons are also quite slow, they are arboreal and may exhibit muscle recruitment patterns related to the specialized grasping and propulsive mechanics (Higham and Jayne, 2004a;Higham and Anderson, 2013;Fischer et al, 2010;Krause and Fischer, 2013;Peterson, 1984). Future work should investigate the activation patterns of the gastrocnemius in other geckos, including arboreal and terrestrial species.…”
Section: Comparisons With Other Lizardsmentioning
confidence: 99%